The level of religiosity and health behaviour of the elderly people. Pilot study - Babik, Kinga; Majda, Anna; Zalewska-Puchała, Joanna; Bodys-Cupak, Iwona (Nursing in the 21st Century, 2021)
THE LEVEL OF RELIGIOSITY AND HEALTH BEHAVIOUR OF THE ELDERLY PEOPLE. PILOT STUDY Introduction. Religiousness supports undertaking positive health behaviors. Aim. Showing the correlation between the level of religiosity and selected pro-health and risky behaviors among the elderly people. Material and methods. As research tools the original questionnaire and Scale of Individual Religion by A. Latała and P. Socha were used. The survey involved 120 participants. Analysis included 64 participants, who were all over 65 years old. U Mann-Whitney test, Kruskal-Wallis test, Spearman’s rank order correlation were used. The level of significance p<0.05 was assumed in the analysis. Results. The studied group of elderly Roman Catholic people was mostly characterized by a high level of religiosity and pro-health behaviors. Correlation between pro-health and risky behaviors of the respondents and their religiosity turned out to be insignificant. However, people characterized by slightly higher level of religiosity declared behaviors such as: not smoking cigarettes, not drinking alcohol, consuming up to three main meals a day, maintain a healthy body weight, not eating between meals, regular doctor and dentist visits, spending little time in front of the TV and computer, being active, using sunscreen, doing self-examination of breasts or testicles once a month and falling asleep at fixed times. Conclusions. The analyses did not confirm that religiosity is an important determinant of pro-health and risky behaviours of the elderly.